2016
DOI: 10.18632/oncotarget.11548
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent mutations in NF-κB pathway components, KMT2D, and NOTCH1/2 in ocular adnexal MALT-type marginal zone lymphomas

Abstract: The pathogenesis of ocular adnexal marginal zone lymphomas of mucosa-associated lymphatic tissue-type (OAML) is still poorly understood. We analyzed 63 cases of such lymphomas for non-synonymous mutations in 24 candidate genes by amplicon sequencing. We validated frequent mutations in the NF-κB regulators MYD88, TNFAIP3 and TNIP1 in OAML, but also identified recurrent mutations in several additional components of the NF-κB pathway, including BCL10 and NFKBIA. Overall, 60% of cases had mutations in at least one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
56
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 54 publications
9
56
2
1
Order By: Relevance
“…Commonly mutated genes are involved in the NF-kB signaling pathway, B-cell differentiation, and epigenetic modification. These findings are in line with those of previous studies although mutation frequency of each gene was variable according to the study [26, 27]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Commonly mutated genes are involved in the NF-kB signaling pathway, B-cell differentiation, and epigenetic modification. These findings are in line with those of previous studies although mutation frequency of each gene was variable according to the study [26, 27]. …”
Section: Discussionsupporting
confidence: 93%
“…KMT2D affects the methylation of lysine 4 on histone H3 ( H3K 4) and the expression of a set of genes, including those involved in the CD40, JAK-STAT, Toll-like receptor and B cell receptor signaling pathways [48]. KMT2D mutations was reported in 22% of ocular MZL in previous study analyzing FFPE samples by targeted deep sequencing [27]. BRD4 is a BET protein linked to the regulation of NF-κB transcriptional activity.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, 2 cases from the Siddiqi et al study were not included, as those cases had demonstrable BCL2/IGH rearrangements. The aggregate frequencies of particular alterations found in dFL were contrasted with previously published reports for cFL (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) and MZL (26,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). Although the previous studies describing CNVs in cFL used a variety of techniques, most of these studies (8/13, 61%) were performed using SNP-array platforms similar to the present method indicating that the results obtained in these prior studies should be comparable to our findings.…”
Section: Crebbp and Stat6 Co-mutation And 16p13 And 1p36 Loss Represementioning
confidence: 88%
“…Studies to date show no or rare somatic mutations of CD79A, CD79B, CARD11, BIRC3, TRAF3 and TNFRSF11A in MALT lymphoma [142,144], further distinguishing MALT lymphoma from other B-cell lymphomas characterized by constitutive NF-jB activation.…”
Section: Somatic Mutationsmentioning
confidence: 99%
“…In a recent study using targeted sequencing, recurrent mutations were identified in NOTCH1 (8%) and NOTCH2 (8%) in ocular adnexal MALT lymphoma [142]. The majority of these mutations…”
Section: Mutations In the Notch Signalling Pathwaymentioning
confidence: 99%